John Milton : The Self and the World - Shawcross, John T. (Book collections on Project MUSE., 1993)
The facts of John Milton's life are well documented, but what of the person Milton -- the man whose poetic and prose works have been deeply influential and are still the subject of opposing readings? John Shawcross's ""different"" biography depicts the man against a psychological backdrop that brings into relief who he was -- in his works and from his works. While the theories of Freud, Lacan, Kohut, and others underlie this pursuit of Milton's ""self, "" Jung and some of his followers provide the basic understanding by which Shawcross places Milton in the panorama of history. His explorations o.